Impact of Leadership Style on Organizational Citizenship Behavior: The Moderating Role of Emotional Intelligence - Adhikari, Madhav; Tiwari, Badri; Thapa, Saara (The Batuk, 2025)
Leadership plays a crucial role in shaping employee behavior and fostering organizational effectiveness. This study examined the impact of leadership styles; autocratic, democratic, and transformational on Organizational Citizenship Behavior (OCB). Additionally, it explored the moderating role of emotional intelligence (EI) in this relationship. The paper employed a descriptive and causal research design. Data were collected from 245 employees working in Nepalese organizations using a structured questionnaire. Mean, standard deviation, correlation analysis, and regression analysis were used to analyze data. Constructs were validated through Cronbach’s alpha. The results found that transformational and democratic leadership styles positively influence OCB, while autocratic leadership has a negative impact. Moreover, EI significantly moderates these relationships by enhancing the positive effects of democratic and transformational leadership while reducing the adverse impact of autocratic leadership. This study contributes to the existing literature on leadership and OCB by integrating the moderating role of EI. It provides valuable insights for Nepalese organizations to adopt leadership styles that cultivate a more engaged and proactive workforce.